A sterilization method for human decellularized vaginal matrices - Jayson Sueters; Leonie de Boer; Freek Groenman; Judith A. F. Huirne; Theo H. Smit; Sebastian A. J. Zaat (Scientific Reports)
Abstract Vaginal reconstruction is necessary for various congenital and acquired conditions, including vaginal aplasia, trauma, tumors, and gender incongruency. Current surgical and non-surgical treatments often result in significant complications. Decellularized vaginal matrices (DVMs) from human tissue offer a promising alternative, but require effective sterilization to ensure safety and functionality. This study aimed to develop a sterilization method for decellularized human vaginal wall scaffolds. Based on our previously implemented decellularization technique with minor modifications, we designed and examined three sterilization methods consisting of (i) chemical decellularization, (ii) decellularization with additional peracetic acid/hydrogen peroxide (PAA/H2O2); (iii) decellularization with antibiotic and antimycotic (AAE) based treatment. Sterilization efficacy was evaluated through controlled contamination with common vaginal microbes and sterility testing subsequent to each sterilization method. The extracellular matrix (ECM) structure was assessed via histological staining. Decellularization alone reduced some added bacterial contaminants but did not achieve complete sterilization. PAA/H2O2-sterilization resulted in severe ECM damage, rendering it unsuitable. The AAE-treatment demonstrated effective sterilization without compromising the ECM structure. Combined decellularization and AAE-based treatment forms a viable sterilization method for human vaginal wall tissue, maintaining ECM integrity and achieving effective micro-organism elimination. This method holds potential for clinical application in vaginal transplantation.